2019
DOI: 10.2147/cmar.s226733
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Intraoperative Prediction Of Non-Sentinel Lymph Node Metastasis Based On The Molecular Assay In Breast Cancer Patients</p>

Abstract: PurposeThe aim of the study is to construct an intraoperative nomogram for the prediction of non-sentinel lymph node (NSLN) metastasis based on the one-step nucleic acid amplification assay in breast cancer patients.MethodsA total of 552 patients were enrolled in the training study and 1090 patients were enrolled in the validation study. The nomogram was constructed based on the molecular assay with logistic multivariate regression analysis in the training study and was validated in the validation study.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The nomogram for prediction of non-SLN metastasis incorporated three parameters: TTL, tumor size, and a twocomponent histopathologic variable (HER2-negative tumor plus Ki67 of ≤ 20%). TTL and tumor size are parameters common to nomograms predicting non-SLN metastasis developed by other investigators [24][25][26]. For example, Shimazu and colleagues' intraoperative nomogram included TTL (log TTL) and tumor size (non-binary) as predictive variables [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nomogram for prediction of non-SLN metastasis incorporated three parameters: TTL, tumor size, and a twocomponent histopathologic variable (HER2-negative tumor plus Ki67 of ≤ 20%). TTL and tumor size are parameters common to nomograms predicting non-SLN metastasis developed by other investigators [24][25][26]. For example, Shimazu and colleagues' intraoperative nomogram included TTL (log TTL) and tumor size (non-binary) as predictive variables [25].…”
Section: Discussionmentioning
confidence: 99%
“…While the ACOSOG Z001 trial demonstrated that ALND can be avoided in a select group of SLN-positive patients [ 27 ], patients who have received NST such as those in our study do not meet ACOSOG Z001 criteria, and indeed application of these criteria seems to exclude the majority of SLN-positive patients [ 25 ]. Since an OSNA assay to determine TTL and thus non-SLN involvement can be performed intraoperatively [ 25 , 26 ], it can also offer the advantage of clinical decision-making during primary surgery, avoiding a second surgery for ALND if required.…”
Section: Discussionmentioning
confidence: 99%